2018
DOI: 10.1007/s00442-018-4153-z
|View full text |Cite
|
Sign up to set email alerts
|

Mate familiarity and social learning in a monogamous lizard

Abstract: Social learning is thought to be advantageous as it allows an animal to gather information quickly without engaging in costly trial-and-error learning. However, animals should be selective about when and whom they learn from. Familiarity is predicted to positively influence an animal's reliance on social learning; yet, few studies have empirically tested this theory. We used a lizard (Liopholis whitii) that forms long-term monogamous pair bonds to examine the effects of partner familiarity on social learning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…In contrast, other studies have reported similar or higher seed germination of offspring in response to better water conditions in the maternal environment (Breen & Richards, 2008; Pias et al, 2010; Yang et al, 2011). However, Mojzes et al (2018) showed that offspring seed germination in the winter annual grass Secale sylvestre was not influenced by the environmental conditions associated with their mother plants. The offspring seed germination of E. gmelinii was negatively correlated with high reproduction effort among their mother plants, which could prevent most of the seed germination occurring with a single year and contribute to the formation of a persistent soil seed bank.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In contrast, other studies have reported similar or higher seed germination of offspring in response to better water conditions in the maternal environment (Breen & Richards, 2008; Pias et al, 2010; Yang et al, 2011). However, Mojzes et al (2018) showed that offspring seed germination in the winter annual grass Secale sylvestre was not influenced by the environmental conditions associated with their mother plants. The offspring seed germination of E. gmelinii was negatively correlated with high reproduction effort among their mother plants, which could prevent most of the seed germination occurring with a single year and contribute to the formation of a persistent soil seed bank.…”
Section: Discussionmentioning
confidence: 96%
“…3 and 4). Similarly, some water manipulation experiments in arid and semiarid ecosystems showed that reductions in the amount of rainfall usually limit plant growth and/or seed production, whereas an increased water supply has the opposite effect (Breen & Richards, 2008; Volis, Ormanbekova & Yermekbayev, 2015; Mojzes et al, 2018). The response of E. gmelinii root/shoot ratio to rainfall amount was consistent with that of plants growing in arid regions, in which increased allocation to roots may be advantageous for capturing limiting soil resources (Padilla et al, 2013; Gao et al, 2015; Shan et al, 2018; Chen et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations